Experiential Marketing: Challenges and Opportunities - Jashwant, Sandeep (Integrated Journal for Research in Arts and Humanities, 2024)
Experiential marketing emerges as a dynamic and influential strategy, providing immersive engagements that captivate consumers and foster brand loyalty. However, executing such strategies successfully presents numerous challenges. This abstract delves into the complex landscape of implementing experiential marketing, highlighting the hurdles and uncovering the vast opportunities. businesses face logistical intricacies, budget constraints, and the need for innovative technological integration. additionally, maintaining authenticity and ensuring scalability pose significant challenges. nevertheless, experiential marketing holds abundant prospects, including forging deep emotional connections with consumers, fostering brand loyalty, and driving word-of-mouth marketing. through industry insights and case studies, this paper provides strategic guidance to overcome these challenges and leverage opportunities. It advocates for a comprehensive approach balancing creativity with feasibility, using data-driven insights to tailor experiences resonating with diverse audiences. emphasizing continuous innovation and adaptability, this abstract serves as a roadmap for marketers navigating the experiential marketing landscape to drive meaningful engagement and brand growth.